Hubungan antara intensitas penggunaan media sosial dengan tingkat nomofobia pada peserta didik SMA - Enjelina Patricia Lala; Angela Fitriani Clementine Kalesaran; Wulan Pingkan Julia Kaunang (Holistik Jurnal Kesehatan, 2026)
Background: Advancements in digital technology and the rising use of smartphones have made social media an integral part of adolescent life. Excessive social media use can increase smartphone dependency, potentially triggering nomophobia—a condition characterized by anxiety or fear resulting from the inability to use a smartphone or a loss of access to communication networks. High levels of social media usage among adolescents are suspected to be linked to increased levels of nomophobia. Purpose: To analyze the relationship between the intensity of social media use and the level of nomophobia among high school students. Method: This study employed a quantitative, analytical, cross-sectional design. It was conducted in January 2026 at State Senior High School 1 Langowan. The study sample consisted of 76 respondents selected using proportional stratified random sampling. Data collection was carried out using the Social Media Usage Intensity Scale (SIPMS) and the Nomophobia Questionnaire (NMP-Q). Data analysis involved univariate and bivariate methods, specifically the Spearman Rank correlation test. Results: The majority of respondents demonstrated high social media usage intensity (89.5%) and experienced severe levels of nomophobia (60.5%). Bivariate analysis revealed a significant relationship between social media usage intensity and nomophobia levels among students (p-value = 0.019; r = 0.268), indicating a weak positive correlation. Conclusion: There is a significant relationship between the intensity of social media use and the level of nomophobia among high school students. Higher intensity of social media use is associated with higher levels of nomophobia experienced by the students.   Keywords: Adolescents; Nomophobia; Smartphones; Social Media Intensity.